A study on the purchase intention of non bumiputera in family Takaful products / Nasrina Ismail - Ismail, Nasrina (Faculty of Business and Management, 2015)
This project paper is prepared as a fulfilment of the Bachelor of Business Administration (Hons) Insurance. The topic for this study is “A Study on the Purchase Intention of Non-Muslims in Family Takaful Products”. The main objective of this study is to examine the perceptions and level of awareness of the non-muslims towards Takaful. The problem statement of this study would be to identify what are the factors influencing the purchase intention of Non-Muslims towards Takaful products. The target population of this study is Universiti Teknologi Mara (UiTM) Lecturers in Malacca Campus. Total of 100 respondents will be approached and used as the sampling in this research. In this research it was found that the awareness of the benefits of the medical and health insurance were influence by three which are income, age and education.